Journal Academic System Management Berbasis Website Di Sekolah Dasar Negeri 012 Langgini - Qori Imanda (Universitas Pahlawan Tuanku Tambusai, 2022)
School is an educational institution that organizes formal education levels, either in the form of public schools, which are managed by the government or the private sector. In carrying out teaching and learning activities, schools aim to educate students under the supervision of teachers. School data processing is still done manually, so there are still many discrepancies in data management. The purpose of this research is to facilitate the school in managing academic data using a website that can be accessed easily. The research method used is the prototype method. And the design of this system uses the Unified Modeling Language (UML). The programming language used is PHP Framework Laravel and MySQL database. So that in this study the academic management system to process data from SDN 012 Langgini becomes more efficient.